2012
DOI: 10.4067/s0716-97602012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Protects the Heart, Lungs and Kidneys from Oxidative Stress under Intermittent Hypobaric Hypoxia in Rats

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is the main secretory product of the pineal gland in all mammals including humans, but it is also produced in other organs. It has been previously demonstrated to be a powerful organ-protective substance under oxidative stress conditions. The aim of this study was to evaluate the protective effect of melatonin in several organs such as heart, lung, kidney, and of the reproductive system, such as testis and epididymis in animals exposed to intermittent hypobaric hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
2
25
2
Order By: Relevance
“…Further, it have been also described that melatonin, another recognized endogenous antioxidant, counteracted the damage of the testis and spermatogenesis in rats subjected to ICH [53]. However, results of our group showed that melatonin had no protective effect in testis and epididymis damaged, despite its amphiphilic nature, and its action of ROS scavenger [54,55].…”
Section: Reproductive Responses and Treatmentcontrasting
confidence: 78%
“…Further, it have been also described that melatonin, another recognized endogenous antioxidant, counteracted the damage of the testis and spermatogenesis in rats subjected to ICH [53]. However, results of our group showed that melatonin had no protective effect in testis and epididymis damaged, despite its amphiphilic nature, and its action of ROS scavenger [54,55].…”
Section: Reproductive Responses and Treatmentcontrasting
confidence: 78%
“…It have been also described that melatonin (10 mg kg À1 body weight) counteracted the testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregon et al, 2010). However, our results showed that melatonin had no protective effect in testis and epididymis damaged (Farias et al, 2012). Melatonin has been shown to exert a protective effect against lipid peroxidation under oxidative stress (Serel et al, 2004).…”
Section: Antioxidants For Spermatogenesis Under Intermittent Hypobaricontrasting
confidence: 76%
“…These findings support the assumption that melatonin may adversely affect sperm quality. The protective oxidative damage of melatonin under an intermittent hypobaric hypoxia is organ-dependent and had no protective effect in testis and epididymis damage (Farias et al, 2012).…”
Section: Antioxidants For Spermatogenesis Under Intermittent Hypobarimentioning
confidence: 99%
“…[14] In addition, reports have indicated protective effects of melatonin on renal functions. [17][18][19] However, exact pathophysiology of sepsisrelated AKI remains unclear and, in spite of new treatment options, AKI continues to occur with high mortality. [20] The aim of the present study was to research effects of agomelatine, a melatonin analogue, on sepsis-induced AKI.…”
Section: Introductionmentioning
confidence: 99%